Innovations in SMEs and conducting e-business : technologies, trends and solutions - Cruz-Cunha, Maria Manuela, 1964-; Varajao, Joao, 1972- (Hershey, PA : Business Science Reference, 2011)
'This book discusses the main issues, challenges, opportunities and solutions related to electronic business adoption with a special focus on SMEs, providing researchers, scholars, and professionals with some of the most advanced research developments, solutions and discussions of E-Business challenges, impacts and opportunities'--Provided by publisher.
'Premier reference source'--Cover.
Includes bibliographical references and index.
Keywords: Small business -- Technological innovations; Electronic commerce